PKM KELOMPOK PENGELOLA SUMBERDAYA ALAM PESISIR KOTA PAREPARE - Hamsiah, Hamsiah; Asbar, Asbar; Danial, Danial; Asmidar, Asmidar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, 2022)
The impacts that occur due to the loss of mangrove forests are very wide, both biological (impact on ecosystems), economic and physical impacts that have a direct impact on the condition of coastal land. This science and technology for the community aims to provide knowledge to each coastal natural resources management group (PSDA) of Parepare City, through a training process on coastal community-based mangrove ecosystem management. This service was carried out from March to July 2018 in the coastal area of Parepare City, precisely in Bumi Harapan Village and Wattang Bacukiki Village. The approach method offered to support IbM activities is counseling accompanied by mangrove planting with a participatory method where partners are directly involved, starting from preparation to the end of the activity. The result in the form of ibm program activities is training. Within the framework of mangrove forest management and preservation, there are two main concepts that can be applied, namely the concept of mangrove forest protection and mangrove forest rehabilitation. The stage of training activities carried out in community-based mangrove ecosystem management in Parepare City is to follow standards by providing modules for mangrove ecosystem management materials. The process of training participants is made in the systematics of the material divided by the topic of the material. The type of output that will be produced based on the activity plan in the research skim proposal of this IbM program is a scientific publication.